2022
DOI: 10.1097/pai.0000000000001049
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Use of an SS18-SSX Antibody for Molecular Assays in Synovial Sarcoma

Abstract: Synovial sarcoma is an aggressive malignancy that generally affects adolescents and young adults and is characterized by high rates of recurrence and metastasis, with a 10-year survival rate of about 50%. The fusion oncoprotein SS18-SSX, the product of a pathognomonic chromosomal translocation t(X;18), is the oncogenic driver of this sarcoma, disrupting differentiation through widespread epigenetic dysregulation. Experimental research into SS18-SSX biology has been limited by the lack of an antibody that speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The first goal we aimed at in this study was to confirm the high sensitivity and specificity of the SS18-SSX antibody in the diagnosis of SS in a retrospective cohort of SSs and its histological mimickers. Our results report a sensitivity of 95% and a specificity of 100% and are thus in perfect agreement with recently published data 13,17,19,22 27 . In the largest reported series (400 tumors including 100 SSs and 300 mimics), Baranov et al who suggested for the first time that the IHC approach could replace molecular investigations to support SS morphological diagnosis 19 have obtained values perfectly overlapping with those presently reported.…”
Section: Discussionsupporting
confidence: 93%
“…The first goal we aimed at in this study was to confirm the high sensitivity and specificity of the SS18-SSX antibody in the diagnosis of SS in a retrospective cohort of SSs and its histological mimickers. Our results report a sensitivity of 95% and a specificity of 100% and are thus in perfect agreement with recently published data 13,17,19,22 27 . In the largest reported series (400 tumors including 100 SSs and 300 mimics), Baranov et al who suggested for the first time that the IHC approach could replace molecular investigations to support SS morphological diagnosis 19 have obtained values perfectly overlapping with those presently reported.…”
Section: Discussionsupporting
confidence: 93%
“…Our patient on the most recent clinical follow-up is 1) is extremely broad and includes NUT carcinoma, melanoma, neuroendocrine neoplasm, myoepithelial carcinoma, SMARCA4-deficient neoplasms, synovial sarcoma, and plasma cell neoplasm. [19][20][21][22][23][24][25][26][27][28][29][30] Immunohistochemical stains and/or molecular testing will be essential. That said, the tumor immunoreactivity with NUT comes with a caveat.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis based on the epithelioid and rhabdoid/plasmacytoid morphology (Table 1) is extremely broad and includes NUT carcinoma, melanoma, neuroendocrine neoplasm, myoepithelial carcinoma, SMARCA4‐deficient neoplasms, synovial sarcoma, and plasma cell neoplasm 19–30 . Immunohistochemical stains and/or molecular testing will be essential.…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin embedding, sectioning, and H&E staining were performed according to standard protocols at the UBC ACS Diagnostic & Research Histology Laboratory. FFPE tissues were also utilized for SS18::SSX IHC, as previously described 57 . Briefly, 4 um sections were subjected to heat-induced antigen retrieval for 20 min, followed by SS18::SSX antibody (1:300, 72364, Cell Signalling Technology) incubation for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%